Traditionally utilization of Selaginella; field research and literature review - AHMAD DWI SETYAWAN (Nusantara Bioscience, 2009)
Abstract. Setyawan AD. 2009. Traditionally utilization of Selaginella; field research and literature review. Nusantara Bioscience 1: 146-158. The aims of this research were to find out traditional usage of Selaginella in medication and its other usages, especially in Java and other Indonesian Archipelago. About 200 of 700-750 world species of Selaginella was found in Indonesian Archipelago. Field research and literature review indicated that Selaginella is used traditionally to heal wound, bloody stools, internal hemorrhoid bleeding, menstrual and uterine disorder, blood expediting, enhancing body endurance and longevity of live, headache, etc. Besides that, some of Selaginella are also used as raw dishes vegetable, ornamental pants, and crafts materials. The utilization of Selaginella is very limited against the amount of species and medicinal potency, it is needed an advance study on ethnobotany and phytochemistry to improve their uses.